2012
DOI: 10.1111/j.1574-6968.2012.02641.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron acquisition in the marine actinomycete genusSalinisporais controlled by the desferrioxamine family of siderophores

Abstract: Many bacteria produce siderophores for sequestration of growth‐essential iron. Analysis of the Salinispora genomes suggests that these marine actinomycetes support multiple hydroxamate‐ and phenolate‐type siderophore pathways. We isolated and characterized desferrioxamines (DFOs) B and E from all three recognized Salinispora species and linked their biosyntheses in S. tropica CNB‐440 and S. arenicola CNS‐205 to the des locus through PCR‐directed mutagenesis. Gene inactivation of the predicted iron‐chelator bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…S. tropica genome sequences maintain two gene clusters predicted to encode siderophore biosynthesis (sid3 and sid4) that are not found in S. arenicola (Supplementary Table S3 and S5), suggesting an additional investment in iron uptake by this species. Although the inactivation of key genes in the S. tropica sid3 and sid4 clusters did not affect growth in iron-limited media (Roberts et al, 2012), these pathways may have a role in the acquisition of other limiting metals (Bellenger et al, 2008) or be regulated by factors other than iron limitation, and thus enhanced siderophore production could help support higher growth rates in this species. The conservation of sid3 and sid4 among all 12 S. tropica strains for which genome sequences were available suggests that there are strong selective pressures to maintain the functions provided by the products of these pathways.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…S. tropica genome sequences maintain two gene clusters predicted to encode siderophore biosynthesis (sid3 and sid4) that are not found in S. arenicola (Supplementary Table S3 and S5), suggesting an additional investment in iron uptake by this species. Although the inactivation of key genes in the S. tropica sid3 and sid4 clusters did not affect growth in iron-limited media (Roberts et al, 2012), these pathways may have a role in the acquisition of other limiting metals (Bellenger et al, 2008) or be regulated by factors other than iron limitation, and thus enhanced siderophore production could help support higher growth rates in this species. The conservation of sid3 and sid4 among all 12 S. tropica strains for which genome sequences were available suggests that there are strong selective pressures to maintain the functions provided by the products of these pathways.…”
Section: Discussionmentioning
confidence: 89%
“…However, two additional siderophore gene clusters (sid3 and sid4) were also identified in S. tropica CNB-440 (Penn et al, 2009). The production of desferrioxamines B and E was later confirmed for both S. tropica and S. arenicola and linked to the des locus (Roberts et al, 2012). A MultiGeneBlast analysis revealed that all 12 S. tropica strains for which genome sequences are available possess all four of the siderophore gene clusters, whereas the 12 S. arenicola genomes chosen for this study only possess the des and sid2 clusters (Supplementary Table S3).…”
Section: Bioinformatic Analysesmentioning
confidence: 93%
See 1 more Smart Citation
“…The desferrioxamine family, a group of hydroxamate siderophores, 22 includes over 50 congeners, including acylated derivatives have only been detected from Streptomyces strains before. 11b, 23 The staurosporine molecular family 24 consists of a total of 11 members, mainly produced by Salinispora strains, but hydroxystaurosporine was also found in Streptomyces CNQ-149.…”
Section: Resultsmentioning
confidence: 99%
“…Previous CID fragmentation studies have provided diagnostic, nominal/accurate mass information for iron (III) bound and apo (unbound) siderophores at the MS and MS 2 level and include several common ferrioxamines such as B, G, D 2 , and E (Figure 1a, b) [10][11][12][13][14]. The iron (III) unbound state is frequently more abundant in bacterial extracts and has therefore been more widely studied.…”
mentioning
confidence: 99%